2013
DOI: 10.1007/s00066-013-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-course radiotherapy in elderly patients with glioblastoma: feasibility and efficacy of results from a single centre

Abstract: Our findings suggest that a hypofractionated accelerated schedule can be a safe and effective option in the treatment of GBM in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our suggestions confirm those reported by Mineo et al 2007 who also revealed that the influence of radiotherapy on survival was greater than the influence of age [16] . Also, it has been suggested that the hypofractionated radiotherapy can be a safe and effective option in the treatment of GBM in elderly patients with a KPS >70 [37,38] . Additionally, Johnson et al revealed that patients not treated with radiation therapy had extremely poor prognoses, with a median survival following diagnosis of approximately 3 months [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Our suggestions confirm those reported by Mineo et al 2007 who also revealed that the influence of radiotherapy on survival was greater than the influence of age [16] . Also, it has been suggested that the hypofractionated radiotherapy can be a safe and effective option in the treatment of GBM in elderly patients with a KPS >70 [37,38] . Additionally, Johnson et al revealed that patients not treated with radiation therapy had extremely poor prognoses, with a median survival following diagnosis of approximately 3 months [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this schedule could reduce discomfort for the patients, reducing the number of days patients must devote to RT and possibly improving their quality of life (19).…”
Section: Introductionmentioning
confidence: 99%
“…In elderly patients, however, concomitant temozolomide should be used more cautiously [ 13 ]. Fariselli et al suggest a hypofractionated regimen with 45 Gy as a safe option for elderly patients [ 14 ]. However the Nordic trial and NOA-08 suggest additionally a monotherapy with temozolomide for elderly patients with a methylated MGMT promoter sequence [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%